2011
DOI: 10.1007/s00125-011-2257-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual risk assessment and information technology to optimise screening frequency for diabetic retinopathy

Abstract: Aims/hypothesis The aim of this study was to reduce the frequency of diabetic eye-screening visits, while maintaining safety, by using information technology and individualised risk assessment to determine screening intervals. Methods A mathematical algorithm was created based on epidemiological data on risk factors for diabetic retinopathy.Through a website, www.risk.is, the algorithm receives clinical data, including type and duration of diabetes, HbA 1c or mean blood glucose, blood pressure and the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(209 citation statements)
references
References 31 publications
7
198
2
2
Order By: Relevance
“…Rates of incidence and progression of retinopathy are greater in people with a longer duration of diabetes and with poor glycaemic control (higher HbA 1c ) and may also vary with other factors such as blood pressure and diabetes type. It has been shown in Denmark that it is possible to identify those at higher absolute risk of STDR, 59 and this suggests that it may be possible to identify subgroups of those with diabetes in whom the screening interval can be extended without risk of STDR developing before the next screening visit. This Danish model was constructed using published data from several clinical trials for which patients were recruited in the 1970s and 1980s and followed into the 1990s.…”
Section: Proposed Time Period For Retention Of Relevant Documentationmentioning
confidence: 99%
“…Rates of incidence and progression of retinopathy are greater in people with a longer duration of diabetes and with poor glycaemic control (higher HbA 1c ) and may also vary with other factors such as blood pressure and diabetes type. It has been shown in Denmark that it is possible to identify those at higher absolute risk of STDR, 59 and this suggests that it may be possible to identify subgroups of those with diabetes in whom the screening interval can be extended without risk of STDR developing before the next screening visit. This Danish model was constructed using published data from several clinical trials for which patients were recruited in the 1970s and 1980s and followed into the 1990s.…”
Section: Proposed Time Period For Retention Of Relevant Documentationmentioning
confidence: 99%
“…A risk calculator has been developed for SA conditions in collaboration with Prof. Einar Steffansson, who developed a risk calculator based on the outcomes observed in a large Danish cohort. [2] Systemic risk is calculated and the outcome drawn onto a 'rev counter' that is placed next to the 'no retinopathy' photographs ( Fig. 1).…”
Section: Fig 1 Examples Of the Ossa Dr Screening System Taken From mentioning
confidence: 99%
“…It has been shown that healthcare costs increase with the severity of diabetic retinopathy , which suggests that preventing its progression may lower healthcare expenditure [7]. In addition, information technology based on epidemiological data may facilitate an individualised determination of screening intervals for diabetic retinopathy [8].…”
Section: Introductionmentioning
confidence: 99%